Percepções dos multiplicadores internos do conhecimento sobre os processos de aprendizagem organizacional dos quais são agentes - Cassal, Maria Vanessa Prates (Universidade do Vale do Rio dos Sinos, 2016)
The theme of knowledge and discuss strategies that promote learning in the workplace gain importance in the current organizational context characterized by rapid change. This article aims to analyze the role of professionals working as Knowledge Multipliers in promoting learning in a hospital in the metropolitan region of Porto Alegre, seeking to characterize the performance of these and their perceptions about the processes and identify skills needed for this role. a descriptive study was based on a quantitative survey by the Survey research method. As a result it was found that the Multipliers understand the importance of their role and show themselves committed, assuming the role of agents in the transmission of organizational knowledge both in times of formal and informal learning. Regarding the skills needed to act in this role, there was great emphasis on communication skills, responsibility, organization, planning and posture.
Keywords: Multiplicadores do conhecimento; Temática do conhecimento; Transmissão do conhecimento organizacional; Competências de Comunicação; Knowledge multipliers; Transmission of organizational knowledge